Imaging-based definition of lower uterine segment carcinoma to improve the detection sensitivity of probable Lynch syndrome. (20th January 2020) - Yamazaki, Hiroyuki; Takeshita, Sho; Todo, Yukiharu; Matsumiya, Hiroko; Shimada, Chisa; Minobe, Shinichiro; Tsuruta, Tomohiko; Kato, Hidenori
Abstract: Objective: The aim of this study was to investigate a magnetic resonance imaging-based definition of lower uterine segment carcinoma. Methods: We retrospectively reviewed 587 consecutive patients with endometrial cancer who underwent hysterectomy. Lower uterine segment carcinoma was determined through pathological examination and magnetic resonance imaging assessment. For imaging assessment, the location of the inner lining of the uterus was classified into four equal parts on a sagittal section image. A tumor was defined as lower uterine segment carcinoma when its thickest part was located in the second or the third part from the uterine fundus. Lower uterine segment carcinoma was further divided into lower uterine segment in a narrow sense, upon which diagnosis was exclusively based on pathological findings, and lower uterine segment in a broad sense that were the remaining lower uterine segment carcinomas except lower uterine segment carcinomas in a narrow sense. The relationship between lower uterine segment carcinoma and probable Lynch syndrome was investigated. Patients with loss of MSH2, MSH6, and PMS2 expression or those with tumors with loss of MLH1 and absence of MLH1 promoter methylation were diagnosed as probable Lynch syndrome. Results: Lower uterine segment carcinoma was identified in 59 (10.2%) patients. Twenty-eight (47.5%) patients were categorized as lower uterine segment in a narrow sense and 31 (52.5%) as lower uterine segment in a broad sense. Among them, probable Lynch syndrome was identified in 12 (20.3%) cases. There was no difference in clinical profiles, including the prevalence of probable Lynch syndrome between the two categories. Conclusions: A magnetic resonance imaging-based expanded definition of lower uterine segment carcinoma is likely to secure characteristics equivalent to a conventional pathology-based definition of lower uterine segment carcinoma. The novel definition of lower uterine segment carcinoma might improve the detection of probable Lynch syndrome. Abstract : Magnetic Resonance Imaging-based definition of lower uterine segment carcinoma might improve the detection of Lynch syndrome-related endometrial cancer.